Treatment of self-injury correlated with mechanical restraints - Kahng, SungWoo; Abt, Kimberly A.; Wilder, David A. (Behavioral interventions, 2001)
Mechanical arm restraints were used to decrease hand‐to‐head self‐injurious behavior (SIB) exhibited by a 16‐year‐old female with severe mental retardation. Although mechanical restraints reduced hand‐to‐head SIB, they were correlated with an increase in other topographies of SIB (e.g., head banging). These other topographies were not significantly affected by the addition of an environmental enrichment procedure, but were immediately and almost completely suppressed when contingent exercise was added. Copyright © 2001 John Wiley & Sons, Ltd.